1990
DOI: 10.1016/0735-1097(90)90623-w
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic factor in patients with right ventricular infarction

Abstract: To determine the possible role of atrial natriuretic factor in right ventricular infarction, serial measurements of this hormone were performed in 21 patients with acute inferior myocardial infarction. All patients underwent enzymatic, electrocardiographic, echocardiographic and coronary arteriographic studies. Ten patients also had right heart hemodynamic measurements. Eight patients had evidence of an associated right ventricular infarction (Group I) and 13 patients did not (Group II). Enzymatically estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 47 publications
0
5
0
2
Order By: Relevance
“…These patients are at increased risk of death, shock, and arrhythmias (8,9). Currently ST segment elevation in the right precordial leads, particularly RV4, is the most powerful predictor of RV involvement in the setting of inferior wall MI (3,10). The sensitivity of this finding is lower than specificity and even when strictly employed, however, the criteria lead to underestimation of the true incidence of right ventricular infarction.…”
Section: Discussionmentioning
confidence: 73%
“…These patients are at increased risk of death, shock, and arrhythmias (8,9). Currently ST segment elevation in the right precordial leads, particularly RV4, is the most powerful predictor of RV involvement in the setting of inferior wall MI (3,10). The sensitivity of this finding is lower than specificity and even when strictly employed, however, the criteria lead to underestimation of the true incidence of right ventricular infarction.…”
Section: Discussionmentioning
confidence: 73%
“…Verschiedenste Untersuchungen zeigten ebenfalls, dass links-und rechtsventrikuläre Infarzierungen ein potenter Stimulus für erhöhte ANP-Ausschüt-tungen sind (5,18,22,26,29). Die erhöhten ANP-Konzentrationen bei Ischämie scheinen mit der ventrikulären Dysfunktion sowie mit dem atrialen Druck und der atrialen Dehnung als stärkstem Reiz für die ANP-Ausschüttung positiv korreliert zu sein (10,14,22).…”
Section: Atrial Natriuretic Peptide (Anp)-levels Reveal Mild Postoperunclassified
“…Mehrere international veröffentlichte Studien beschäftigen sich mit der Rolle des ANPs im Zusammenhang mit ischämischen Ereignissen am Myokard und der Frage, ob die Konzentrationsverläufe dieses Hormons zur Einschätzung der kardialen Funktion herangezogen werden können (1,5,7,19,21,22,27,28). Auch die Rolle des TnTs in der Bypasschirurgie zur Abschätzung des myokardialen Schadens und als Verlaufsmarker für die Beeinträchtigung der Funktion des linken Ventrikels und des oxidativen Metabolismus wurden mehrfach untersucht (12,13,25).…”
Section: Diskussionunclassified
“…'7 21 Furthermore, disproportionately high plasma concentrations of atrial natriuretic peptide have been observed in patients with myocardial infarction extending to the right ventricle, suggesting that the peptide may have a pathophysiological role in the clinical right ventricular infarction syndrome. 22 Of the three natriuretic peptides, the rise in C-ANP concentration seems to be most abrupt after myocardial infarction. Plasma concentration of C-ANP has usually reached its peak value at the time of admission, and, in uncomplicated infarctions, it usually returns to near normal values within hours or a few days.…”
Section: Natriuretic Peptidesmentioning
confidence: 99%